Prevalence of dengue NS1 antigenemia among healthy blood donors in a tertiary care hospital in Southern India - Remi Remakanth (Wolters Kluwer Medknow Publications, 2021)
INTRODUCTION: Transmission of dengue by transfusion of blood products has been documented, although the frequency of these occurrences and the level of viremia required to cause clinical dengue are unknown. The primary objective was to assess the prevalence of dengue NS1 antigen among healthy blood donors at our blood center.METHODOLOGY: This was a cross-sectional study conducted in the Department of Transfusion Medicine, a tertiary care hospital in South-eastern India, from February 2019 to January 2020. A total of 968 donor samples were included in the study. Dengue NS1 antigen detection was done using enzyme-linked immunosorbent assay. Data regarding clinical, epidemiological, and demographic characteristics were collected from the donor questionnaire and records.RESULTS: In the study, the overall prevalence of Dengue NS1 antigen was 0.9%, with nine positive samples among the 968 samples tested. Eight of them were male, and 1 was a female donor. All of them were in the age group <32 years. Half of the positive donors were detected during December-January, the immediate post rainy season in this part of the country. Two-third of the positive donors were from rural areas.CONCLUSION: This study with a 0.9% throws light on the seroepidemiological prevalence of dengue among asymptomatic donors and gives an insight into whether dengue screening is required to be implemented in routine transfusion transmissible infection screening in blood transfusion services and shall assist in devising strategies to be adapted as to improve the blood safety.